PENGARUH MODEL PEMBELAJARANTHINK TALK WRITE (TTW) PADA MATERI SISTEM EKSKRESI TERHADAP HASIL BELAJAR SISWA DI SMP BINA GUNA TANAH JAWA - Sulindayani; Rosenta Purba, Ika; Tridelpina Purba, Sumarny (Jurnal Metabio, 2023)
This study aims to determine the effect of the Think Talk Write learning model on the excretory system on student learning outcomes for SMP Bina Guna Tanah Jawa. The Think Talk Write learning model is intended to improve learning outcomes and facilitate student understanding of the excretory system. This study is a quasi-experimental study. The population was all 66 eighth-grade students. Subjects were randomly selected, with class VIII 1, consisting of 32 students, serving as the control class, and class VIII 2, consisting of 34 students, serving as the experimental class. Data collection consisted of a pretest and posttest. The results showed that the Think Talk Walk learning model significantly impacted science learning outcomes in the excretory system. The difference in science learning outcomes between students participating in the Think Talk Write (TTW) learning model and those participating in conventional learning (t = 10.973 > t = 1.69) suggests that the Think Talk Write learning model has a positive effect on student learning outcomes.